ESTIMATING PROFIT , COST FUNCTION AND TECHNICAL EFFICIENCIES OF RICE PRODUCTION IN NEJAF FOR SEASON 2016* - & Mahmood, Al-Mashhdani (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
The aim of this study was to estimate the profit and cost functions as well as economic, price, cost, and technical efficiencies beside the other economic indices at actual, optimal and profit-maximizing output of rice. A random sample of 240 rice  farms in Nejaf province was used during the agricultural season 2016. From efficiency scales of profit function, it was shown that the output quantity had the greatest impact on the profit compared to other variables (average output costs and price). According to the cost function, the optimum output level and the profit- maximizing output  level for the short run were 64.84 tons and 117.4 tons respectively. The lowest price that the farmer can accept was 194.83 thousand dinars / ton. At this price, the producer loss all fixed costs in the short run, hoping that the price of rice will improve in the long run. Net profit was estimated on the basis of actual output, cost minimizing output (optimal) and profit-maximizing output, which amounted to 8084.32, 30852.65 and 45547.5 thousand dinars, respectively. The of technical efficiency were 34%. and the cost efficiency was 0.52. We conclude from the study that economic resources have not been exploited optimally, indicating that actual output is far from optimal output. The study recommends a output policy aimed at increasing economic efficiency and optimizing the use of available resources.